Implementasi Zero Trust Arsitektur Pada Jaringan Hybrid Work - Rakhmadi Rahman, Rakhmadi Rahman; Faiz Ilyas, Muhammad Faiz Ilyas; Syawal, Muhammad Syawal (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Riau, 2025)
The increasingly common hybrid working model poses significant challenges to network security and the protection of sensitive data. Traditional perimeter-based security approaches are no longer effective because they rely on the assumption that internal devices can be trusted. This research proposes a Zero Trust Architecture (ZTA)-based solution that promotes the principle of ‘never trust, always verify’ to address these challenges. The ZTA system is designed and implemented in a hybrid environment using components such as WireGuard as a VPN, UFW as a firewall, and Keycloak integrated with the Flask application as an OIDC-based identity management system. Through a pre-test and post-test experimental approach with controls, the effectiveness of the system was tested before and after the implementation of ZTA. The test results showed significant improvements in terms of unauthorized access detection, network communication protection through encryption, and user authentication reliability. Thus, the implementation of ZTA is proven to be able to increase system resilience to cyber threats in a dynamic and decentralized hybrid work environment.